Home enteral nutrition for patients with esophageal cancer undergoing esophagectomy: A systematic review and meta-analysis - Zhang, Chi; Hu, Li-Wen; Qiang, Yong; Cong, Zhuang-Zhuang; Zheng, Chao; Gu, Wen-Feng; Luo, Chao; Xie, Kai; Shen, Yi (Frontiers in Nutrition, 2022)
Introduction: Home enteral nutrition (HEN) is a relatively new nutritional intervention that provides patients with enteral nutrition support at home through jejunostomy or nasogastric feeding tubes. We conducted this systematic review and meta-analysis to explore the safety and effect of HEN compared with normal oral diet (NOD) in postoperative patients with esophageal cancer (EC) Methods: EMBASE, Medline, Web of Science and the Cochrane Library were used to search articles in English-language journals. The intervention effect was expressed using risk ratios (RR) for dichotomous outcomes and mean differences (MD) for continuous outcome measures, with 95% confidence intervals (95% CI). Chi-square test and I-Square was used to test heterogeneity among studies. Results: Four studies were eventually included in this meta-analysis. Compared with NOD, HEN has a favorable impact on postoperative BMI (WMD = 0.70, 95% CI: 0.09 ~ 1.30, P = 0.02), LBM (WMD = 0.76, 95% CI: 0.04 ~ 1.48, P = 0.04), ASMI (WMD = 0.30, 95% CI: 0.02 ~ 0.58, P = 0.03). Physical function (WMD = 9.26, 95% CI: 8.00 ~ 10.53, P < 0.001), role function (WMD = 9.96, 95% CI: 8.11 ~ 11.82, P < 0.001) and social function (WMD = 8.51, 95% CI: 3.48 ~ 13.54, P = 0.001) of HEN group were better than those of NOD group at 3 months, and HEN could reduce the fatigue of patients (WMD = -12.73, 95% CI: -14.8 ~ -10.66, P < 0.001) and the incidence of postoperative pneumonia (RR = 0.53, 95% CI: 0.34 ~ 0.81, P = 0.004). No significant difference in albumin between HEN and NOD groups (WMD = 0.05, 95% CI: -0.03 ~ 0.13, P = 0.20) Conclusion: HEN improved nutritional status and quality of life (QOL) in postoperative patients with EC, reduced fatigue and the incidence of postoperative pneumonia. All in all, the results of our meta-analysis support the use of HEN after esophagectomy.